Recruitment processes in West Greenland waters : with special focus on Greenland halibut (Reinhardtius hippoglossoides, W.) - Stenberg, Claus (Marine Biology, 2007)
The topic of this thesis is recruitment processes in Greenland Halibut (Reinhardtius hippoglossoides) in West Greenland waters. The focal point is Greenland halibut’s early life history from oocytes in the female ovary - to larvae living in the pelagic - to juveniles on the sea bottom. These early life stages are examined in four studies: Ovary and oocyte development in adult female Greenland halibut was studied in Davis Strait, Disko Bay and Baffin Bay. The objective of this study was to track and compare ovary development from winter to autumn from the inshore fjords of Disko Bay, Baffin Bay and the presumed spawning area in Davis Strait. Results showed that maturity was much more progressed in Davis Strait compared to the two other areas. Furthermore, almost all adult female fish in Davis Strait showed signs of maturation while only a fraction of the larger females (>80 cm length) were mature in Disko and Baffin Bay. A large proportion of the Greenland halibut in Disko and Baffin Bay did not appear to begin the maturation cycle until very late in their life history and/or were repeat spawners with a multiyear maturation cycle. Thus the observations from Disko and Baffin Bay support the theory that Greenland halibut can have a prolonged adolescent phase. The result from the study also strongly indicated that Davis Strait was the only major spawning area in West Greenland. Larvae distribution and growth of Greenland halibut and Sandeel (Ammodytes sp.) was studied across the West Greenland shelf. The objective of this study was to analyse spatial distribution and growth during three periods May, June and July and relate these to cross shelf variability in biological and hydrographical conditions in order to identify areas of special importance for larval growth and survival. Results showed that in May small Greenland halibut larvae, some still with small remains of the yolk-sac, were primarily distributed offshore in Davis Strait. Their distribution coincided with their prey resources while some vagrant ...